ORAL MANIFESTATIONS OF VITAMIN DEFICIENCIES - Eldefar, Yousra Rafa Abdalla (faculty of Basic Medical Science - Libyan International Medical University, 2018)
Vitamins is play an important and equivocal role in general and oral health, vitamins (both fat soluble and water soluble) are essential for development, maturation and functioning of oral tissues at almost every decade of life.
There are many vitamins which play a major role in normal functioning of the oral cavity and any deficiency of these vitamins from the normal levels will lead to problems in the normal functioning of the human body, there are mainly two types of vitamins fat soluble (which can be stored with other lipids in fatty tissues or in the liver and can build up to toxic levels. Require bile for absorption ex. vitamin A , vitamin D, vitamin E and vitamin K) , and Water soluble (absorbed directly in the blood stream, travel freely and are not stored. Excreted in the urine ex. folate (folic acid), biotin, vitamin B-1, vitamin B-2 , vitamin B-3, vitamin B-5, vitamin B6 , vitamin B12 and vitamin C ) ,Some or most of the vitamins have a direct or indirect role in having a healthy oral cavity